FGFR3 mutations indicate better survival in invasive upper urinary tract and bladder tumours. - van Oers, J; Zwarthoff, E; Rehman, I; Azzouzi, A; Cussenot, O; Meuth, M; Hamdy, F; Catto, J (2009)
BACKGROUND: Promoter hypermethylation and microsatellite instability are frequent in tumours of the upper urinary tract (UTT) and infrequent in bladder tumours. FGFR3 mutations are common findings in bladder tumours and are associated with a good prognosis. OBJECTIVE: To investigate the occurrence of FGFR3 mutations in UTT and determine the prognostic effect of these genetic changes. DESIGN, SETTING, AND PARTICIPANTS: Tissue from the initial tumour was obtained from 280 patients (117 bladder tumours and 163 UTT). Patients were selected from pathologic archives to represent the disease spectrum of UCC throughout the urinary tract. Following UCC excision, patients underwent surveillance for a median of 56 mo (range 1-216 mo) or until death. MEASUREMENTS: FGFR3 mutation analysis was successfully performed on 252 of the 280 primary tumours using the SNaPshot method. Two-tailed statistical analyses were done using the chi(2), Fisher exact tests, and log rank tests. Cox proportional hazard ratios were estimated to obtain risks of recurrence, progression, and death, and to find independent prognostic factors in a multivariate model. RESULTS AND LIMITATIONS: FGFR3 mutations occurred with the same frequency in bladder and upper tract tumours. Mutations were associated with low-stage tumours and a milder disease course in bladder, ureter, and renal pelvis tumours. Strikingly, our data suggest that these mutations indicate a better survival in patients with invasive tumours from the bladder and upper urinary tract. CONCLUSIONS: FGFR3 mutation status might be used to select patients with invasive UCC who have a lower risk of death.